Plutarch, On the Daimonion of Socrates: Human Liberation, Divine Guidance, and Philosophy. Scripta Antiquitatis Posterioris ad Ethicam Religionemque pertinentia (SAPERE) 16. - Lamberton, Robert (Bryn Mawr Classical Review, 2010)
The article reviews the book "Plutarch, On the dominion of Socrates: Human Liberation, Divine Guidance and Philosophy," edited by Heinz-Gunther Nesselrath.